Peranan Guru PAI dalam Meningkatkan Kedisiplinan Shalat Berjamaah Siswa - Azis, Abdul; Abnisa, Almaydza Pratama (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to find out the Role of PAI Teachers in Improving Student Congregational Prayer Discipline. This study uses a descriptive method with data collection techniques using field observation, interview, and documentation methods. Data analysis was carried out qualitatively consisting of data reduction, data presentation, and conclusion drawn. The results of the analysis show that PAI teachers have a very strategic role in efforts to improve the discipline of congregational prayer among students. Through a comprehensive understanding, good example, and intensive mentoring, PAI teachers can be the driving force for the formation of a strong attitude of discipline and commitment to students to perform congregational prayers. The importance of continuous education and training for teachers to improve their skills and insights cannot be ignored in today's linear series. PAI teachers must remain relevant to developments in the world of education and continue to develop as professionals. PAI teachers have a very strategic role in efforts to improve the discipline of congregational prayer among students. Through a comprehensive understanding, good example, and intensive mentoring, PAI teachers can be effective agents of change in shaping the disciplined and religious character of students